Diagnosis and Genetic Counseling for Mitochondrial Disease at the Institute of Medical Genetics, Tokyo Women's Medical University - IWASAKI, Naoko; MATSUO, Mari; SAITO, Kayoko (Tokyo Women's Medical University Journal, 2018)
We performed a retrospective review of medical records of patients seeking genetic counseling for mitochondrial disease at our clinic between 2004 and 2015. Of a total of 31 adult subjects (male to female ratio= 1 : 2.1; mean age at first visit 40 years), 27 (87.1 %) underwent genetic testing. The results of the genetic testing revealed a gene mutation causing the mitochondrial disease in 20/27 (74.1 %) subjects. The mutation detection ratio in blood samples from symptomatic subjects was 17/22 (77.3 %). The mutation detection ratio differed according to family history of mitochondrial disease. Of the 31 subjects, 13 (42.0 %) learned that they had at-risk family members based on the results of their own genetic testing. Eight female subjects who were single or without a child or pregnant underwent genetic counseling to obtain a precise diagnosis and identify the genetic cause based on a detailed family history and other medical information. The genetic cause in these cases was usually not identified. Even in the case of a precise diagnosis, there may not be sufficient natural history information, which makes presymptomatic and prenatal genetic testing difficult. For subjects with mitochondrial disease and their families, uncertainty about their future leads to great emotional stress. Our findings indicate the importance of providing clear information about the disease and its uncertainties, empathetically listening to the patients, and assisting patients with the process of adapting to their situation. Long-term follow-up is necessary to track changes in symptoms or in family situations, as well as to detect new cases.